DIGITAL COMICS (WEBTOON) FOR EFL READING COMPREHENSION: LEARNER PREFERENCES AND PERCEPTUAL FACTORS - Muhammad Rizal Afandi; Putu Dian Danayanti Degeng (Universitas Bina Bangsa Getsempena, 2025)
This research investigates the preferences and perceptions of English learners toward the use of digital comics as a medium for enhancing reading comprehension. Using a descriptive quantitative approach, the data were collected from 100 participants mixed between 50 high school students and 50 university students with prior experience in digital comic usage. A four-point Likert scale questionnaire was used to collect the data, then the data that was collected explained by a descriptive quantitative method. The data were analyzed using a descriptive quantitative to provide a clear overview of participants’ perceptions based on the Likert-scale. The findings revealed that the majority of the students preferably use webtoon instead of other digital comics for learning. The findings can be reported that digital comics significantly improve reading comprehension, facilitate vocabulary acquisition, and engage more compared to traditional reading materials. More than half of the respondents agreed or strongly agreed with statements across all of the statements, indicating consistently positive perceptions. Engagement and motivation were strongly influenced by the visual and interactive features of digital comics, while language proficiency and prior experience emerged as key factors shaping perceptions. The results highlight the potential of digital comics as an innovative learning media that makes reading more interesting. These findings highlight the pedagogical value of digital comics especially webtoon in language education to improve both comprehension and learner motivation.